Konsep Pendidikan Karakter Anak Dalam Keluarga Disorot dari Surat Apostolik “Amoris Laetitia” - Kwirinus, Dismas; Saeng, Valentinus (Vocat : Jurnal Pendidikan Katolik, 2023)
The focus of this research examines "Implementation of Christian educational values and the responsibility of the laity for the development of priestly vocations among young people". Attention to priesthood vocations among young people requires concrete steps. Unity in concrete action is very necessary. Efforts that can and may be made such as fellowships and services to grow the priesthood towards the values and vocation of life as priests, among young Catholics. This paper aims to describe and analyze the involvement of the laity in the development of priestly vocations among young people. The author uses a descriptive qualitative method which produces data in the form of words and written or spoken from the people and the observed behavior. As for the findings of this paper, that the participation of the laity in developing priestly vocations among young people is evident in parish life. The genuine attention and openness of the people towards priestly vocations among young Catholics will be felt by those who have directed themselves to a life as priests.